Real Voices, Real Learning: Students’ Perceptions of Authentic Listening Materials - Nuralisa, Nuralisa; Qalyubi, Imam; Ali Mirza, Akhmad (Journal of English Language and Education, 2025)
Listening comprehension is a critical skill in EFL education, yet it often receives less attention than other language skills. Traditional listening materials frequently fail to reflect real-world language use, limiting their effectiveness in developing learners’ listening proficiency. Despite the recognized benefits of authentic listening materials, there is limited research on students' perceptions of their effectiveness in improving listening skills. This study aims to investigate the perceptions of MA Hidayatul Insan students regarding the use of authentic listening materials. Using a mixed-methods approach, data were collected through a structured questionnaire completed by 100 students and interviews with five participants. The findings reveal that students perceive authentic materials as engaging and beneficial for improving listening skills, vocabulary, and understanding of native speakers. However, challenges such as the difficulty level of the materials and lack of familiarity with native speech patterns were noted. The study concludes that incorporating authentic materials can enhance listening proficiency, emphasizing the need for tailored strategies to address these challenges.